Parametric study of tunnel analysis in clay shale on short term and long-term conditions using finite element method - Danang Setiya Raharja; I Wayan Sengara; Imam Achmad Sadisun (Himpunan Ahli Teknik Tanah Indonesia, 2022)
This study aims to determine the characteristics and classification of clay shale in West Java and their implications for tunnel stability under short and long-term conditions using the finite element method. Data were collected from projects in West Java containing clay shale spread over four rock formations, namely Cihoe (Tpc), Subang (Tms), Cantayan (Mtts/Mttc), and Jatiluhur (Tmj). Each formation has varying mechanical and engineering properties. The value of SPT from Cihoe formation can be categorized in three conditions, SPT < 40, SPT 40-60, and SPT > 60 for fully, highly to moderately, and slightly weathered, respectively. Meanwhile, the value of SPT of Subang formation can be categorized in two conditions, SPT < 60 and SPT >60 for fully and highly weathered, respectively. The data collected were analyzed to determine the Mohr-Coulomb (MC) and Hardening Soil (HS) parameters for Plaxis modeling. The model applied three variations of overburden thickness between 3 times, 6 times, and 9 times the tunnel diameter (3d, 6d, and 9d respectively). The greater the overburden thickness, the lower the surface deformation. The HS model gives better results than the MC model because it considers non-linearity. The minimum effective parameters needed to support tunnel during construction to meet the allowable deformation for 3d overburden conditions and the particular reinforcement system are c' 53kPa, ϕ' 28°, and E'50ref 30,000 kPa. Long-term conditions possess lower stability than short-term, while prolonged deformations increase after construction and provide a rise in tunnel lining stress that needs to be considered in the design stage. The application of 2D tunnel modeling needs to be carefully analyzed, thereby representing the behavior of a continuous or 3D tunnel structure.